Immunoendocrine response to cycling following ingestion of caffeine and carbohydrate - Walker, G.; Finlay, O.; Griffiths, H.; Sylvester, J.; Williams, M.; Bishop, N. C. (Medicine & Science in Sports & Exercise, 2007)
Purpose: This study investigated the effect of caffeine consumed with and without carbohydrate (CHO) on immunoendocrine responses after exercise.